2016
DOI: 10.13189/ujer.2016.041318
|View full text |Cite
|
Sign up to set email alerts
|

Technology Leadership of Education Administers and Innovative Technologies in Education: A Case Study of Çorum City

Abstract: In this global world in which educationaltechnologies have developed at such a great pace, it is possible to say that administrators in the education sector are obliged with serious roles with regard to keeping up with the evolving technology and the management of education in this virtual environment. In the present study utilizing screening research method, technologic leadership attitudes of administrations in educational domain were investigated. The survey titled "Technology Leadership of Education Admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…According to the studies in the literature on whether the technological leadership differs in terms of gender according to school administrators are (Aktaş, 2016;Banoğlu, 2011;Brunson, 2015;Bülbül & Çuhadar, 2012;Cantürk, 2016;Curnyn, 2013;Depew, 2015;Doğan, 2018;Duncan, 2011;Görgülü, 2013;Gürkan, 2017;Güven, 2015;Hayytov, 2013;Kör, 2016;Şişman-Eren, 2010;Ulukaya, 2015;Uçkan, 2010;Uysal-Balaban, 2012;Yorulmaz, 2016). In these studies, it was concluded that the technology leadership competencies of school administrators don't differ in terms of their gender (Alkdrem, 2014;Beyaz, 2014;Brunson, 2015;Bülbül & Çuhadar, 2012;Can, 2008;Cantürk & Aksu, 2017;Çakır & Aktay, 2018;Görgülü, 2013;Gürkan, 2017;Güven, 2015;Hayytov, 2013;Ölçek, 2014;Şişman-Eren, 2010;Uçkan, 2010;Ulukaya, 2015;Uysal-Balaban, 2012).…”
Section: Results Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the studies in the literature on whether the technological leadership differs in terms of gender according to school administrators are (Aktaş, 2016;Banoğlu, 2011;Brunson, 2015;Bülbül & Çuhadar, 2012;Cantürk, 2016;Curnyn, 2013;Depew, 2015;Doğan, 2018;Duncan, 2011;Görgülü, 2013;Gürkan, 2017;Güven, 2015;Hayytov, 2013;Kör, 2016;Şişman-Eren, 2010;Ulukaya, 2015;Uçkan, 2010;Uysal-Balaban, 2012;Yorulmaz, 2016). In these studies, it was concluded that the technology leadership competencies of school administrators don't differ in terms of their gender (Alkdrem, 2014;Beyaz, 2014;Brunson, 2015;Bülbül & Çuhadar, 2012;Can, 2008;Cantürk & Aksu, 2017;Çakır & Aktay, 2018;Görgülü, 2013;Gürkan, 2017;Güven, 2015;Hayytov, 2013;Ölçek, 2014;Şişman-Eren, 2010;Uçkan, 2010;Ulukaya, 2015;Uysal-Balaban, 2012).…”
Section: Results Conclusion and Recommendationsmentioning
confidence: 99%
“…When the researches on the technological leadership of school administrators are examined, the participants; from school administrators (Aktaş, 2016;Alkrdem, 2014;Banoğlu, 2011;Brunson, 2015;Bülbül & Çuhadar, 2012;Curyn, 2013;Aktay & Çakır, 2018;Çalık, Demirsoy, 2016;Depew, 2015;Doğan, 2018;Duncan, 2011;Şişman-Eren, 2010;Gültekin, 2013;Gürkan, 2017, Güven, 2015Hayytov, 2013;Kör, Erbay, & Engin, 2016;Uçkan, 2010;Ulukaya, 2015;Yorulmaz-Can, 2016), from teachers ( Baş, 2012;Durnalı, 2018;Engür, 2014;Ertuğrul, 2014;Gençay, 2018;Gerçek, 2016;Görgülü, 2013;Gürkan-Beyaz, 2014;Karabağ-Köse, Yurdakul, & Onuk, 2017;Irmak, 2015;Ölçek , 2014;Öztaş, 2013;Samancıoğlu et al, 2015;Sincar, 2009), it is also seen that it consists of both teachers and administrators (Balaban, 2012;Cantürk, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dieser Aspekt wird von mehreren Studien sowohl bezogen auf die Leitungsebene als auch auf die Ebene der Lehrkräfte angeführt. 11 Wissen und Erfahrungen könnten in einem Netzwerk bestmöglich ausgetauscht werden (Agélii Genlott et al, 2019;Kör, Erbay & Engin, 2016). Weitere Punkte, die unter den Aspekt des Austausches und der Zusammenarbeit subsumiert werden können, sind Arbeitsteilung und eine Kultur des Teilens, die durch den Einsatz digitaler Medien befördert werden (Eickelmann & Gerick, 2017;Razak et al, 2018;Vermeulen, Kreijns, van Buuren & van Acker, 2017).…”
Section: Förderliche Aspekte Für Die Medienintegration Im Rahmen Der Schulentwicklung -Medienintegration Voranbringenunclassified
“…(Sheninger, 2019, Vorwort).Schulleiterinnen und Schulleiter sind relevante Akteure, um Schule im Kontext des digitalen Wandels zu transformieren. Neben allgemeinen Führungskompetenzen(Cole & Sauers, 2018;Gilmore & Deos, 2020) benötigen sie ebenfalls technologische Kompetenzen(Claro, Nussbaum, López & Contardo, 2017; Håkansson Lindqvist & Petersson, 2019;Kör et al, 2016;Öznacar & Dericioglu, 2017;Schwanenberg et al, 2018). In der aktuellen Forschung wird in diesem Zusammenhang von technology oder digital leadership 23 gesprochen.…”
unclassified
See 1 more Smart Citation